Three new species of Phaeoramularia from India - and A.N. RAI, K.K. GADPANDEY, D.K. DWIVEDI (Indian Phytopathology, 2002)
During surveys of plant diseases of forest flora in Madhya Pradesh, India, 3 new species of Phaeoramularia, P. asclepiadacearum, P. cacesalipiniacearum and P. verbinacearum, were identified and are described.